PROTOTYPE PEMBERSIH KACA OTOMATIS BERBASIS INTERNET OF THINGS PADA INDOMARET CAILE - Nur Asnin; Farida; Sri Asfirawati Halik (Institut Teknologi dan Bisnis Bina Adinata, 2024)
This thesis aims to: (1) Design an Internet of Things-based Automatic Glass Cleaner prototype at Indomaret Caile, and Use the blynk Application, (2) Know the Implementation of an Internet of Things-based Automatic Glass Cleaner prototype at Indomaret Caile. This study uses the prototype research method, where the stages are as follows: (1) Needs Analysis. (2) Making prototypes. (3) prototype Evaluation. (4) Coding system. (5) system Testing. (6) system Evaluation. (7) Using the system. Based on the results of this study it was concluded that: (1) The Internet of Things-based Automated Glass Cleaner prototype at Indomaret Caile was designed using 4 components, namely: 1 GP2Y1010AU0F Dust sensor as a sensor for dust detection, 1 Water Pump to circulate water in the glass area, and 1 Scraping Wiper glass cleaner, and 2 Stepper Motors that will drive the Scraping Wiper. (2) The Internet of Things-based Automatic Glass Cleaner prototype at Indomaret Caile where the Dust sensor GP2Y1010AU0F will detect dust that has entered the Dust sensor according to the amount of dust that has been set at least 0.01 mg/m3, then the Water Pump will automatically flowing water towards the glass for 6 seconds after that the Stepper Motor will move the Scraping Wiper from the bottom up for 75 seconds, besides that the Esp32-Cam will display the condition of the window glass through the blynk application, and based on the results of the Validation it is found that all aspects declared to have a fairly high validity, which is worth 0.86, so that the working process of the tool works optimally.